Reaksi Pasar Atas Pengumuman Paket Kebijakan Ekonomi X Tentang Daftar Negatif Investasi - Rosita Dewi, Gusti Ayu Surya; Wirama, Dewa Gede; Rasmini, Ni Ketut (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 2 (2017), 2017)
ABSTRACT This study aims to empirically test the market reaction that occurs upon the announcement of Economic Policy Package X about the negative investment list (DNI). This study using event study method. The market reaction is calculated using cumulative abnormal return (CAR). The population used are all companies listed on the Indonesian Stock Exchange (BEI), 525 companies. The number of samples used are 477 companies. The analysis technique used is the one sample t-test and the independent sample t-test.  The analysis showed that there is a positive market reaction to the announcement of the Economic Policy Package X. Furthermore, there are differences in the reaction that occurs between the business sectors that benefited by the policy than other business sectors. The highest reaction is shown by the business sectors that benefited by the policy. Business sectors which are benefited by the policy announcement obtained higher market reaction than their counterpart. Keywords: Market reaction, economic policy package X, negative list investment, abnormal return